Assessment of the impact of residential urban patterns of different hillslopes on urban drainage systems and ecosystem services in the Federal District, Brazil - Brito, Leticia Karine Sanches (2020)
In Brazil, stormwater management systems are usually deficient and very commonly implemented after the urban areas have settled. In Brasilia, the Federal capital of Brazil, this problem is aggravated due to the fact that the rainy and dry seasons are very well defined, thereby increasing the importance of groundwater recharge as an ecosystem service. This research aims to evaluate the impact of urban structure types and topographies in stormwater management and three ecosystem services: groundwater recharge, flooding, and water quality. The urban patterns studied included mixed residential areas with two block positions (orthogonal and parallel to the topography) and a single-family house with low density. The studied landforms include a divergent-convergent surface and a flat hillslope with high slope taxa—strictly convergent and strictly divergent surfaces, respectively. The arrangement of landforms has an impact on runoff generation, with an average of 9% during peak flow, and an infiltration capacity, on average, 3% higher in the divergent-convergent surface. The greatest impact of the topography on stormwater management is considered based on the direct cost of the drainage system, which is 44% higher in the flat hillslope. Low impact development (LIDs) devices helped to improve ecosystem service provisions and even presented efficiency that almost achieved that of the predevelopment conditions in the evaluated scenarios. Seeking the urban patterns that best suit given environmental conditions is one of the approaches studied in this paper.